Worthy Opponents - Steel, Danielle; Braun, Michael (Actor) ([Ashland, OR] : Blackstone Publishing, 2023)
Spencer Brooke always knew she was destined to be CEO of her grandfather's business, the most respected and luxurious department store in New York City. Mike Weston is known for making enormous profits by transforming small businesses into bigger, more successful ones. And Brooke's feels like the perfect opportunity. Yet the firm's beautiful and savvy CEO turns down the offer before they even meet. But when bad luck strikes, suddenly she is backed into a corner.
Keywords: Department stores -- Fiction; Inheritance and succession -- Fiction; Divorced women -- Fiction; Single mothers -- Fiction; Families -- Fiction; Man-woman relationships -- Fiction; New York (N.Y.) -- Fiction; Audiobooks; Domestic fiction